Autopsy Findings in an Elderly Man Suffering from Severe von Willebrand’s Disease - Kernoff, Leslie M; Rose, Alan G; Hughes, Jane; Jacobs, Peter (Thrombosis and Haemostasis, 1981)
A platelet derived growth factor released following platelet adhesion to the subendothelium of damaged arteries may promote the development of atherosclerotic lesions. Consequently patients with von Willebrand’s disease in whom platelet adhesion is abnormal may be protected from atherosclerosis. This possibility was investigated by performing an autopsy study on an elderly patient who had suffered from severe von Willebrand’s disease. Extensive atherosclerotic lesions were found at post mortem suggesting that platelets may not play a clinically significant role in the causation of atherosclerosis
Keywords: von Willebrand’s disease; Atherosclerosis